The Role of al-Hamid Clan in Islamic Affairs at Petuanan Namatota and Petuanan Kumisi in Kaimana, West Papua - Affan, Muhammad; Suaedy, Ahmad; Alnizar, Fariz; Muhtarom, Ahmad (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
There have been many studies on Islam and Islamic societies in Papua. However, there have not been many studies on Arab descendants in Papua. Nevertheless, people of Arab descent have long been present in Papua and have played a significant role in developing the Islamic community in Papua. Therefore, discussing their role in the Papuan Muslim community is important. Based on this issue, the following article examines Papuans from the Al-Hamid clan in two chiefdoms in Kaimana, namely Petuanan Namatota and Petuanan Kumisi. The main issue discussed in this research is the Al-Hamid clan's role in Islamic affairs in the Namatota and Kumisi Chiefdoms in Kaimana. The research data were obtained through a literature review and fieldwork in Kaimana, West Papua. The results show that Papuans of Arab descent from the Al-Hamid clan play an important role in religious affairs in the Namatota and Kumisi Chiefdoms. People from Al-Hamid's descendants have been religious teachers, qadhi, mosque imams, and policymakers in Islamic religious affairs in the two chiefdoms since around the end of the 19th Century. Al-Hamid's descendants still carry out these roles, although they are delegated to other parties in some circumstances.